(untitled) (Third Sector Social Economic Review, 2019)
Chain supermarkets are retail enterprises with significant shares in our country and around the world. Almost every consumer makes purchases from these chain supermarkets. Services offered to consumers is a distinguishing factor in this industry with intense competition. Failures made in these services thaht are offered, play a crucial role in establishing brand loyalty and/or the loss of existing consumers. This research is exploratory in nature and focuses on various taypes of failures and how consumers respond to these failures. In-depth interviews are carried out with 15 consumers who have experinced some form of service failure at this supermarket within the past 5 months. The results indicate that the quality of service recovery leads to a forgiving response toward the company in general. When a service failure is properly recovered, consumers loyalty increases. However, loyalty is observed to diminish when recovery is deemed insufficient. The satisfactory level of recovery provided as a result of service failure by chain supermarkets has a major impact on the corporate image as well.